A sulfated polysaccharide from the edible flesh of Cipangopaludina chinensis inhibits angiogenesis to enhance atherosclerotic plaque stability. (March 2020) - Xiong, Qingping; Li, Hailun; Zhou, Li; Liang, Jian; Zhang, Ziyun; Han, Yun; Jing, Yi; Hu, Youdong; Shi, Yingying; Xu, Tingting; Qian, Guoqing; Yuan, Jun
Graphical abstract: Highlights: Sulphated polysaccharide (CCPSs) from Cipangopaludina chinensis can stabilize plaque. CCPSs can significantly reduce vulnerability index of atherosclerotic plaques. CCPSs can significantly inhibit angiogenesis in atherosclerotic plaques. Inhibitory role of CCPSs on angiogenesis was regulated by PI3K/Akt/mTOR pathway. Abstract: Sulfated polysaccharide (CCPSs) of Cipangopaludina chinensis has shown significant antiangiogenic activity. In view of the closely relationship between angiogenesis and atherosclerotic plaque vulnerability, we speculated that CCPSs may stabilize atherosclerotic plaques by inhibiting angiogenesis. The purpose of this study was to demonstrate a correlation between the role of CCPSs in stabilizing plaques and its inhibition of angiogenesis, and further clarify its regulatory mechanism. The results suggested that CCPSs can enhance the stable components and inhibit the vulnerability factors to reduce vulnerability index of atherosclerotic plaques, thus making it more stable. Its mechanism was proved to be closely related with anti-angiogenesis in plaques. This inhibitory effect of CCPSs on angiogenesis in plaques was also found to be achieved by regulating the PI3K/Akt/mTOR signaling pathway. The results indicated that CCPSs is a promising candidate for treatment of atherosclerotic unstable plaques.